(untitled) (Journal of Hama University, 2024)
Introduction and aim of the research: The failure of root canal cementation posts most of the clinical failure cases involving endodontic treated teeth reconstructed with a post and core. Hence, efforts were focused on researching posts as an attempt to develop systems that are bio-receptive and preserve root dentin, do not apply efforts to the root, are strong, can be fixed with dental cement, and are resistant to abrasion. And cosmetic, and this led researchers to develop cosmetic posts made of reinforced resin or porcelain, in an attempt to also get rid of color defects. This research aims to:evaluated the push-out bond strength of glass fiber posts cemented with different luting agents. Materials and Methods: The research sample consisted of 30 mandibular teeth extracted for orthodontic reasons, The specimens were divided into the following 3 groups according to the luting agent used (n=10). The first group utilized FC(HARVARD,Germany) ) to coat the post, whereas the second group used RMGIC (Meron plus QM, VOCO,Germany). whereas the Third group used Resin Cement (ITENA clinical, France) was used as the control. . The specimens were cross-sectioned after 24 h. Specimens were cross-sectioned six millimeters thick into coronal using a sectioning machine. The strength of the bond between the luting cement and the posts was measured using push-out bond strength testing. We loaded the components at a cross speed of 0.5 mm/min on a universal testing machine until the bond failed. Results: The FC group had a 73.53N push-out bond strength, whereas the RMGIC group had a 133.55N, whereas the Resin Cement group had a 137.47N push-out bond strength. Conclusion: FC’s mean push-out bond strength score is lower than RMGIC’s and Resin Cement. Results: The results showed the superiority of both resin cement and resin-modified glass ionomer cement over flowable composites, while no statistically significant differences appeared between resin cement and resin-modified glass ionomer cement.